The influence of location, services, and community culture on patient loyalty with satisfaction as intervening variables in Spirit Dental Clinic Lubuk Pakam – Deli Serdang - Sylvia Sylvia; Efendy Pakpahan; Salman Faris; Syaifuddin Syaifuddin (Privietlab, 2022)
Patient satisfaction is one of the main indicators of health facility standards. Improving the quality of service is absolutely necessary in order to face the era of globalization. The research location was conducted at the Spirit Dental Clinic Pratama Special Dental Clinic, which is located at Jln. Border No. 21 Lubuk Pakam, Deli Serdang. The time of the study was carried out in July – August 2021. The population in this study were all patients who came for treatment at the Spirit Dental Clinic Pratama Special Dental Clinic in July – August 2021. The sample was part of the population consisting of several members of the population. The sample in this study were patients who came for treatment to the Spirit Dental Clinic Pratama Special Dental Clinic for 2 months, namely from July to August 2021 and obtained a total sample of 100 respondents by accident. Based on the results of the research and discussion that have been described, the following conclusions are drawn: Location affects patient loyalty at the Spirit Dental Clinic Pratama Special Dental Clinic, meaning that the better the location of the dental and oral health service provider, the patient's loyalty will increase. Service affects patient loyalty at the Spirit Dental Clinic Pratama Special Dental Clinic, meaning that the better the services provided by dental and oral health service providers, the patient's loyalty will increase. Community culture affects patient loyalty at the Spirit Dental Clinic Pratama Special Dental Clinic, meaning that the better the community culture for dental and oral health services, the patient's loyalty will increase. Location affects satisfaction at the Spirit Dental Clinic Pratama Special Dental Clinic, meaning that the better the location of the dental and oral health service provider, the satisfaction will increase.